2021
DOI: 10.1097/gox.0000000000003441
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Applicant to the Saudi Plastic Surgery Residency Program

Abstract: Background: Securing a plastic surgery position is a demanding task for students. Although many papers have been published internationally discussing the traits and features deemed important from the point of view of plastic surgery program directors, a gap exists in the literature where this aspect is not covered in Saudi Arabia. The aim of this study was to fill this gap. Methods: In this cross-sectional study, a survey was developed targeting all current and former Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Mardan et al’s Saudi study found that research experience is the most important selection criterion. This goes against our study in which communication skills, clinical rotation, and leadership were the most important criteria [ 12 ].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Mardan et al’s Saudi study found that research experience is the most important selection criterion. This goes against our study in which communication skills, clinical rotation, and leadership were the most important criteria [ 12 ].…”
Section: Discussioncontrasting
confidence: 82%
“…In this survey, the majority of PDs regarded the recommendation’s mode of communication such as phone calls as the most crucial component. They considered high-quality publications as more highly preferred applicants who had completed electives or rotations in their department [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, there are limited training options for plastic or reconstructive surgery (16), and it would be advantageous to learn the medical students' attributes, characteristics, and other factors that influence their decision in pursuing this surgical subspecialty. Thus, our study explored the knowledge and perceptions of plastic surgery among medical students pursuing their degree in the Western region of KSA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Saudi residency program directors in competitive specialties, such as plastic surgery, anesthesiology, and urology, prefer candidates who have high-quality research publications. [27][28][29] In contrast, specialties that are relatively less competitive in Saudi Arabia, such as internal medicine, obstetrics and gynecology, family medicine, and pediatrics have fewer publications. 30 This issue extends to the United States as orthopedic residency program applicants list research projects in their resumes as 'submitted'; but, in reality, remain frequently unpublished or published in low-impact journals.…”
Section: Influntial Factors Towards Conducting Medical Researchmentioning
confidence: 99%